Development, implementation and evaluation of a bespoke, advanced practice musculoskeletal training programme within a clinical assessment and treatment service. (5th February 2020) - Stevenson, Kay; Bicker, Greg; Cliffe, Stephanie; Kemp, John; Menon, Ajit; Hall, Emma; Ryan, Sarah
Abstract: Musculoskeletal disease is burdensome, costly and reported to be the 4th biggest reason for years lived with disability. Lower back and neck pain were the leading causes of disability in England from 1990 to 2016. Clinical Assessment and Treatment Services (CATs) have been established to provide expert assessment and management for this group of patients, with the aim of providing the majority of care within primary care, reducing referrals going through to secondary care. Such services require professionals with the appropriate skills and autonomy to fulfil this aim. This paper describes the development, implementation and evaluation of a bespoke Musculoskeletal Trainee programme within a large Clinical Assessment and Treatment Service. A 12‐month training schedule was designed to assist the transition of a Physiotherapist (Band 7) to Advanced Practitioner level (Band 8a). Trainees worked through a series of competencies, captured their experiences and collected evidence of achievement during the 12‐month period. Their experiences were explored using content analysis and common themes were identified. Three Physiotherapists were employed on the basis of undertaking this programme and successfully completed the programme. They highlighted the benefits of the programme being its bespoke nature and its flexibility to reflect their learning needs. Mentorship was a key component as they all identified that progressing to an autonomous role can be challenging. Learning new skills and working differently at a pace that suited them were seen as positives aspects. This programme describes the competencies and experiences of three individuals progressing to Advanced Practice Physiotherapists. This paper may assist those who manage and commission such services.